Examination of student opinions on the use of the my mind notes application created using QR code technology in nursing education in clinical practice - Zehra Belhan; Emine Tuğba Yorulmaz; Vildan Kocatepe; Yasemin Uslu; Nermin Ocaktan; Elif Ezgi Karatepe; Vesile Unver (Elsevier, 2023)
Aim: The aim of this study is to examine the effectiveness of using the "My Mind Notes" application, which was developed to utilize QR code technology, in undergraduate nursing clinical education. Method: This design-based research was conducted with medical-surgical nursing students from a university located in Istanbul (n = 78) between February and July 2021. The information that the student would need in clinical practice was included in the educational material of the QR code. QR codes were utilized throughout the 10-day clinical practice, and students' views were obtained at the end of the practice. The data were collected using the "Student Views on the Effectiveness of My Mind Notes Application" form, which was prepared to align with the literature and expert opinion. The data were analyzed using descriptive statistical methods such as number, percentage, and mean. Results: In their education lives, 78.2 % of the students had never used a QR code application. The students' mean scores of psycho-motor skills, cognitive/theoretical information, and anxiety reduction in clinical practice concerning the My Mind Notes application were 7.76 ± 1.74, 8.34 ± 1.71, and 6.46 ± 2.36, respectively. Conclusion: It is shown that the "My Mind Notes" application prepared using QR code technology helps nursing students become lifelong learners by enriching their learning experiences regardless of time and place.